Anxiety and Depression Symptoms in Patients with Chronic Obstructive Pulmonary Disease - Kirkil, Gamze; Deveci, Figen; Deveci, Suleyman Erhan; Atmaca, Murad (Kure Iletisim Grubu A S, 2015)
Objective: The presence of psychiatric comorbidities in patients with chronic obstructive pulmonary disease (COPD) has been linked to increased mortality and decreased functional status. In the present study, we investigated the frequency of anxiety and depression, and the relationships sociodemographic characteristics, pulmonary function test (PFT) parameters, arterial blood gas (ABG) parameters, and the presence of anxiety and depression in COPD patients. Method: Eighty COPD patients were enrolled in the study. The sociodemographic characteristics, treatments, comorbidities, PFT and ABG results of all cases were recorded. The Beck Depression Inventory (BDI) and the Hospital Anxiety Scale (HAS) were used to rate anxiety and depression. Results: Depression was diagnosed in 42 (52.5%) patients. according to the BDI scores and 51 (63.8%) patients according to the Hospital Anxiety and Depression Scale -Depression Subscale (HAD-D) scores; anxiety was found in 22 (27.5%) patients according to the Hospital Anxiety and Depression Scale -Anxiety Subscale (HAD-A) scores. When evaluated according to COPD stage, depression and anxiety scores were significantly higher in very severe COPD than in moderate COPD (p<0.01 for BDI, p<0.001 for HAD-D, p<0.001 for HAD-A). Moreover, anxiety scores in severe COPD were significantly higher than in moderate COPD (p<0.01), and in very severe COPD than in severe COPD (p<0.01). Significant negative correlations were found between Beck depression scores and FVC values, between HAD-D scores and FEV1, FVC, FEV1/FVC values and between HAD-A scores and FEV1, FVC, FEV1/FVC values. The risk factors for anxiety and depression were found to be living in an urban area and difficulty in falling asleep. Conclusion: We suggest that depressive symptoms are frequently seen in COPD patients and that depression and anxiety can be related to disease stage, disturbances of sleep, and living in an urban area.
Keywords: chronic obstructive pulmonary disease; depression; anxiety